The effect of current public procurement law on duration and cost of construction projects in Turkey - Erdis, Ercan (Journal of Civil Engineering and Management, 2013)
The current public procurement law (Law No. 4734) was established in Turkey in 2003. The current law has fundamental differences from the previous one, Law No. 2886, in that the current law’s main objective is to increase the effective use of public resources. Although the current law was enacted nine years ago, no in-depth research has been undertaken related to the extent of public savings. Thus, the aim of this research is to analyze the performance of public investments for construction with respect to their success in achieving on time and within budget completion. Additionally, a comparison between the completion duration and budget of construction projects undertaken under the current and the previous law is presented. To achieve these goals, historical contract documents addressing 878 and 575 public construction projects undertaken under two laws, respectively, were analyzed. In this context, the data mining method, including decision trees, artificial neural network, and support vector machines, was applied to predict the duration and cost deviations of the construction projects during the tender process, and the results were compared. It was demonstrated that the current law has contributed substantially towards the completion of the projects within estimated or envisaged durations and costs. The findings of this research can be generalized to countries with similar economical and organizational structures with Turkey.